基于OpenGL的齿轮传动数字化设计与仿真 - 杜文辽; 陈学文; 李安生; 李治国 (Jixie chuandong)
Gear transmission is an important branch and gear is used most universally in mechanisms. Considering the constitution of involute gear figure and the character of gear transmission , the accurate mathematical model of 3D geometry model and gear transmission is established. Combined with OpenGL, the 3D geometry for gear and bevel gear is built in Visual C + + , and the simulation of gear transmission is implemented based on OpenGL Double Buffer. The data of gear can also be used in numerical control machining, and the realization of simu-lation of gear transmission has a further value for parametrical design,which validates the validity of the mathematical model of gear. Thismodel can be applied in virtual prototype modeling.